Risk Factors and Long‐Term Outcomes in Horses After the 2021 Outbreak of Equine Herpesvirus 1 Myeloencephalopathy, Valencia, Spain - María de laCuesta‐Torrado; Ana Velloso Alvarez; Isabel Santiago‐Llorente; Lara Armengou; Federico Nieto; José Ríos; Fátima Cruz‐López; Eduard Jose‐Cunilleras (Journal of Veterinary Internal Medicine)
ABSTRACT Background Equine herpesvirus myeloencephalopathy (EHM) is a persistent threat to horses, with unclear risk factors and disease severity. Objectives To evaluate risk factors, effective reproduction rate (Rt), and long‐term athletic outcomes of an EHM outbreak. Methods Retrospective study of the 2021 EHM outbreak in Valencia, Spain, examining associations between risk factors (sex, age, breed, country of origin, and vaccination status) and case fatality rate, EHM development, and odds of returning to competition using odds ratios [95% CI] and Rt via the Robert Kochs Institute method. Results Among 191 horses, 38 (20%) were clinically normal, 13 (7%) were subclinical, and 140 (73%) presented clinical signs (89 EHM, 64%). One hundred sixty horses were isolated at the show, while 47 were treated in hospitals. The mean age was 9.8 ± 3.0 years; 85 (45%) were mares, 79 (41%) geldings, and 27 (14%) stallions. The EHM case fatality rate was 11/89 (12%). Vaccination was associated with EHM development (4.54[2.23–9.27]; OR[95% CI]; p < 0.001) and case fatality rate (3.9[1.1–14.4]; OR[95% CI]; p < 0.043). EHV‐1‐infected horses without EHM were more likely to return to competition (54/61; 89%) than those recovering from EHM (65/89; 73%; p = 0.024). It was initially 4.2 and decreased to < 1 within 2 weeks of the outbreak. Conclusions During the 2021 EHV‐1 outbreak in Valencia, vaccination status appears to be associated with EHM development. Horses recovering from EHM had slightly lower chances of returning to competition than those shedding EHV‐1 without EHM. The high Rt value underscores the contagious nature of EHV‐1.